The epidemiology of dependency among urban-dwelling older people in the Dominican Republic; a cross-sectional survey - Ferri Cleusa P; Rodríguez Guillermina; Rottbeck Ruth; Acosta Daisy; Prince Martin J (BMC, 2008)
Abstract Background Demographic ageing, and the health transition will soon lead to large increases in the number of dependent older people in low and middle income countries. Despite its importance, this topic has not previously been studied. Methods A cross sectional catchment area one-phase survey of health conditions, dependency, care arrangements and caregiver strain among 2011 people aged 65 years and over in Santo Domingo, Dominican Republic Results 7.1% of participants required much care and a further 4.7% required at least some care. The prevalence of dependency increased sharply with increasing age. Dependent older people were less likely than others to have a pension and much less likely to have paid work, but no more likely to benefit from financial support from their family. Needing much care was strongly associated with comorbidity between cognitive, psychological and physical health problems. However, dementia made the strongest independent contribution. Among those needing care, those with dementia stood out as being more disabled, as needing more care (particularly support with core activities of daily living), and as being more likely to have paid caregivers. Dementia caregivers experienced more strain than caregivers of those with other health conditions, an effect mediated by behavioural and psychological symptoms. Conclusion Dependency among older people is nearly as prevalent in Dominican Republic as in developed western settings. Non-communicable diseases, particularly dementia are the main contributing factors. Attention needs to be directed towards the development of age-appropriate healthcare, a long-term care policy, and mechanisms for ensuring the social protection of older persons.